1988
DOI: 10.3109/00016488809125100
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nasal Allergy in Otitis Media with Effusion: A Clinical Study

Abstract: Tomonaga K, KuronoY, Mogi G. The role of nasal allergy in otitis media with effusion. Acta Otolaryngol (Stockh) 1988; Suppl. 458: 4147. In order to clarify the role of Type I immunologic reactions in the etiology of otitis media with effusion (OME), kindergarten and elementary school children were given routine nasal allergy (NA) tests and otologic tests. Several children among them were evaluated for eustachian tube (ET) function before and after the intranasal histamine challenge, using the inflationdefla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
5

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 16 publications
7
54
0
5
Order By: Relevance
“…1b, 2). Other investigators, using objective intradermal and in vitro testing, have demonstrated that 72-100% of the children with OME are atopic: Tomonaga (72%) [26], Nsouli (78%) [27], Hurst (81%) [28], McMahan (93%) [29], Hall (100%) [30]. Statistical analysis evidenced a significant correlation between atopy and OME with a correlation index of r = 0.998 (v 2 = 54.56; P = 1.50 -13 ; OR = 11.16).…”
Section: Resultsmentioning
confidence: 99%
“…1b, 2). Other investigators, using objective intradermal and in vitro testing, have demonstrated that 72-100% of the children with OME are atopic: Tomonaga (72%) [26], Nsouli (78%) [27], Hurst (81%) [28], McMahan (93%) [29], Hall (100%) [30]. Statistical analysis evidenced a significant correlation between atopy and OME with a correlation index of r = 0.998 (v 2 = 54.56; P = 1.50 -13 ; OR = 11.16).…”
Section: Resultsmentioning
confidence: 99%
“…6 In another study, 77 children who had chronic middle ear effusion, and who had had at least one ventilation tube placement performed were followed up. There was increased IgE in the middle ear effusion in 14 out of 32 children with allergic rhinitis, compared with two out of 45 children considered to be non-allergic.…”
Section: Resultsmentioning
confidence: 99%
“…But, OME is the most frequent cause of hearing loss in children Shekelle et al, 2002). An epidemiologic link between OME and AR has been demonstrated in many trials (Alles et al, 2001;Tomonaga et al, 1988). Prevalence of AR among patients with chronic or recurrent OME is higher than that seen in the same age group in the general population.…”
Section: Fig 3 Sinus Cycle Leading To Rs (Adapted Frommentioning
confidence: 98%